Power Dynamics And Identity Politics in the Era of Globalization - Kurniawan, Nanang (International Journal of Education, Information Technology, and Others, 2024)
The era of globalization has brought significant changes to power dynamics and identity politics in various parts of the world. This study analyzes how globalization affects power structures and group identities at the national and international levels. Using a qualitative approach, this research explores the influence of globalization on identity politics through case studies in several countries that have experienced significant political changes in the last two decades. Research results show that globalization not only blurs geographic boundaries but also strengthens the identities of certain groups while weakening others, often triggering conflict and nationalist reactions. On the other hand, globalization also creates opportunities for the emergence of new identities that transcend national boundaries, which can contribute to new forms of power in global politics. The implications of this phenomenon are the expansion and complexity in the negotiation of identity and power, requiring a deeper understanding of how policies can be directed to manage diversity and conflict. This research provides new insights into the interactions between globalization, identity, and power, and offers recommendations for policymakers and practitioners in facing the challenges generated by changing global dynamics.